Adoption of colonoscopy surveillance intervals in subjects who received polypectomy in southern China: A cost‐effectiveness analysis - Deng, Yunyang; Ding, Hanyue; Huang, Junjie; Wong, Martin Chi Sang (Journal of gastroenterology and hepatology, 2023)
Background and Aim We aimed to evaluate the cost‐effectiveness of different colonoscopy intervals among average‐risk (5 vs 10 years) and high‐risk (1 vs 3 years) southern Chinese populations. Methods We constructed a Markov model with a hypothetical population of 100 000 individuals aged 50–85 years. Average risk was defined as 1–2 non‐advanced adenomas (tubular adenoma sized < 10 mm without high‐grade dysplasia). High risk was defined as ≥ 3 non‐advanced adenomas or any advanced adenoma (adenoma sized ≥ 10 mm, with high‐grade dysplasia, or with villous/tubulovillous histology). Three strategies were compared: a 5/1 strategy (average‐risk subjects: 5‐year interval; high‐risk subjects: 1‐year interval), a 10/3 strategy, and a control strategy (a 10/10 strategy). Costs (US dollar), quality‐adjusted‐life‐years, incremental cost‐effectiveness ratio, and net health benefit were calculated. If the incremental cost‐effectiveness ratio of one strategy against another was less than willingness‐to‐pay ($24 302 US/quality‐adjusted‐life‐years), the strategy was more cost‐effective than another. Results Compared with the 10/3 strategy, the 5/1 strategy involved more costs and effects (incremental cost‐effectiveness ratio = $40 044 US/quality‐adjusted life‐years). When the 10/10 strategy was regarded as the control, the 5/1 strategy had a higher incremental cost‐effectiveness ratio than the 10/3 strategy ($26 056 vs $10 344 US/quality‐adjusted life‐years). Furthermore, the 10/3 strategy had the highest net health benefit. Conclusions A 10/3 interval was more cost‐effective than a 5/1 interval. From an economic perspective, our findings supported a 10‐year interval for average‐risk individuals and a 3‐year interval for high‐risk subjects. The findings could help form the optimal colonoscopy interval for average‐risk and high‐risk patients. A 10/3 interval was more cost‐effective than a 5/1 interval. From an economic perspective, our findings supported a 10‐year interval for average‐risk individuals and a 3‐year interval for high‐risk subjects.